The forgotten stent: late complication in a patient with neobladder - Riccardo Autorino; Antonio Maschio; Umberto Pane; Marco De Sio; Luca Cosentino; Giuseppe Quarto; Salvatore Mordente; Ferdinando Di Giacomo; Luigi Santini; Massimo D'Armiento (The Scientific World Journal)
Encrustation constitutes a serious complication of ureteral stent use and can result in difficult stent removal. We report the case of a patient with a retained ureteral stent for 3 years following a radical cystectomy.